2014
DOI: 10.1523/jneurosci.0505-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Classical Inheritance: The Influence of Maternal Genotype upon Child's Brain Morphology and Behavior

Abstract: Genetic variance has been associated with variations in brain morphology, cognition, behavior, and disease risk. One well studied example of how common genetic variance is associated with brain morphology is the serotonin transporter gene polymorphism within the promoter region (5-HTTLPR). Because serotonin is a key neurotrophic factor during brain development, genetically determined variations in serotonin activity during maturation, in particular during early prenatal development, may underlie the observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…However, the maternal genotype has previously been shown to be associated with, for example, the child's brain morphology [32], cognitive development [33], risk of autism [34] and atopic dermatitis [35]. The fact that type 1 diabetes-associated autoantibodies that precede the diagnosis of type 1 diabetes can appear only months after birth [36] suggests a fetal programming of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the maternal genotype has previously been shown to be associated with, for example, the child's brain morphology [32], cognitive development [33], risk of autism [34] and atopic dermatitis [35]. The fact that type 1 diabetes-associated autoantibodies that precede the diagnosis of type 1 diabetes can appear only months after birth [36] suggests a fetal programming of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although all children carried the L/S genotype, somatosensory cortex grey matter density and fine motor task performance were greater in children of the SS mothers [190]. In another human study, familial analyses of the tryptophan hydroxylase 1 gene TpH1 mutation carriers (that have deficiency in serotonin production in the periphery, but not in the brain) revealed that offspring of mothers carrying TpH1 mutations exhibited higher ADHD scores and related symptoms than did controls or offspring of fathers with the corresponding TpH1 mutations [79].…”
Section: Other Parental Influencesmentioning
confidence: 86%
“…Another important factor in fetal neural development is maternal genotype. For example, maternal SERT promoter region 5-HTTLPR genotype affects the development of children, with their neuroimaging phenotypes and cognitive performance differing between the 5-HTTLPR SS and LL mothers [190].…”
Section: Other Parental Influencesmentioning
confidence: 99%
“…It is known that parental genotypes are related to negative parenting behaviours and of course children share the genotypes of their parents [ 29 ]. A recent study found that links between 5-HTTLPR gene of mother and child were related to child brain morphology and behavioural performance [ 46 ].…”
Section: Discussionmentioning
confidence: 99%